Kiai, Seks Dan Relasi Kuasa Pesantren Indonesia (Studi Kasus Jawa Timur) - Almunauwar Bin Rusli; Ahmad Fauzi Fauzi (Prodi Studi Agama-agama Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2026)
The abuse of religious authority occurring in several Islamic boarding schools (pesantren) in East Java has been widely reported by various mass media outlets; however, it has received insufficient in-depth analysis from academics. Consequently, the phenomenon of sexual violence rooted in the power relations of the Kiai (religious leader) has never been seriously addressed by the government. It should be emphasized that this research does not intend to make generalizations and focuses solely on case studies of five problematic pesantren.Using the Systematic Literature Review (SLR) method, critical discourse analysis and sociology of knowledge approach, several key points were identified. First, the weakness of government oversight and the strengthening doctrine of mystical logic serve as the dominant factors explaining the immense power held by the Kiai within pesantren institutions. Second, in response to this crisis, a wave of resistance has emerged from various elements of civil society. This manifests through two primary channels. (1) Internal channels: survivors among the female students (santriwati) have engaged in peer-to-peer communication, self-isolation for protection, and strategic collaborations with lawyers and prosecutor, NGOs, and the mass media to voice the truth (2) External channels: residents of East Java have demanded firm state action, including the implementation of chemical castration, the revocation of operational licenses for problematic pesantren, and curriculum reform aimed at dismantling patriarchy and violence. These conclusions demonstrate that sexual violence in pesantren is not merely a matter of individual morality; it is a systemic issue that necessitates legal intervention, rigorous state supervision, and the deconstruction of doctrines that undermine the human rights of female students